REVEALING RACIAL HEGEMONY IN NIKE ADVERTISEMENT CAMPAIGNS ON YOUTUBE: A SYSTEMATIC MULTIMODAL CRITICAL DISCOURSE ANALYSIS - Rully Syafril Firmansyah (Universitas Sebelas Maret, 2019)
This study investigateshow Nike as one of sport apparel product in America represents racial hegemony through linguistics and visual elements selected in the advertisement campaign. Critical Discourse Analysis framework by Fairclough (1989), Systemic Functional Linguistics by Halliday (2004), Systemic Functional Visual Elements by Kress and van Leeuwen (2006), and theory of hegemony by Gramsci (1999) are appliedto analyse and to elaborate the visual and language patterns used by Nike for the purpose of revealing anracial hegemony especially from advertisement campaign in mass media. The data of this study are taken from YouTube in the form of video. Furthermore, to specify the data, Generic Structure by Halliday and Hasan is applied. Then data are processed by using Systemic Functional Linguistics by Halliday (2004) and Systemic Functional Visual Elements by Kress and van Leeuwen (2006) to analyze linguistics and visual elements in the advertisement.The finding discloses that Nike's choices of language or discourse constructs positive image of the minorities in advertisement campaign. Minorities issues such as race, religion, and the stereotype implicetily of their success of being the best athlete in the world. Nike obviously shows of anti racismwhich gives motivations and labels to the minorities through endorse them with its products in